Difficult laryngoscopy and tracheal intubation: observational study - Rebeca Gonelli Albanez da Cunha Andrade; Bruno Luís Soares Lima; Douglas Kaíque de Oliveira Lopes; Roberto Oliveira Couceiro Filho; Luciana Cavalcanti Lima; Tania Cursino de Menezes Couceiro (Brazilian Journal of Anesthesiology, 2018)
Introduction: Since anesthesia complications associated with unexpected difficult airway are potentially catastrophic, they should be avoided. The modified Mallampati test and jaw-thrust maneuver enable the identification of difficult airway. The aim of this study was to associate the modified Mallampati test and the jaw-thrust maneuver with laryngoscopy (Cormack–Lehane) in an attempt to identify a better predictor of difficult airway in an adult population undergoing elective surgery. Method: A cross-sectional study in which 133 adult patients undergoing elective surgery requiring tracheal intubation were analyzed. The accuracy and specificity of the modified Mallampati test and jaw-thrust maneuver were assessed by correlating them with difficult laryngoscopy (Cormack–Lehane Degrees 3 and 4). Results: In the 133 patients evaluated the difficult intubation rate found was 0.8%; there was association between the two predictive tests proposed (p = 0.012). The values of 94.5% for specificity and 95.4% for accuracy were found for the jaw-thrust maneuver and for the modified Mallampati test, the values found were 81.1% and 81.2%, respectively. Kappa agreement identified a result of 0.240 between jaw-thrust maneuver and Cormack–Lehane, which was considered reasonable. On the other hand, a poor agreement (κ = 0.06) was seen between modified Mallampati test and Cormack–Lehane test. Conclusion: The jaw-thrust maneuver presented superior accuracy and agreement than the modified Mallampati test, showing the ability to identify a difficult airway. It is necessary to emphasize the association of tests in the evaluation of patients, emphasizing their complementarity to minimize the negative consequences of repeated laryngoscopies. Resumo: Introdução: As complicações anestésicas associadas às vias aéreas difíceis inesperadas por serem potencialmente catastróficas devem ser evitadas. O teste de Mallampati modificado e a manobra de protrusão mandibular possibilitam a identificação da via aérea difícil. O objetivo deste estudo foi associar o teste de Mallampati modificado e a manobra de protrusão mandibular com a laringoscopia (Cormack-Lehane) e tentar identificar um melhor preditor de via aérea difícil na população adulta submetida à cirurgia eletiva. Método: Estudo corte transversal, foram analisados 133 pacientes adultos submetidos a cirurgias eletivas que necessitavam de intubação orotraqueal. Avaliaram-se a acurácia e especificidade do teste de Mallampati modificado e da manobra de protrusão mandibular, correlacionados com laringoscopia difícil (Cormack-Lehane Graus 3 e 4). Resultados: Entre os 133 pacientes avaliados, a taxa de intubação difícil encontrada foi 0,8%, houve associação entre os dois testes preditores propostos (p = 0,012). Foram encontrados os seguintes valores para a especificidade 94,5% e a acurácia 95,4% na manobra de protrusão mandibular. Já para o teste de Mallampati modificado valores de 81,1% e de 81,2% respectivamente. A análise de concordância Kappa identificou entre manobra de protrusão mandibular e Cormarck-Lehane um resultado de 0,240; considerado razoável. Por outro lado, observou-se uma fraca (κ = 0,06) concordância entre o teste de Mallampati modificado e o Cormarck-Lehane. Conclusão: A manobra de protrusão mandibular apresentou acurácia e concordância superiores ao teste de Mallampati modificado, mostrou a capacidade de identificar uma via aérea difícil. Faz-se necessário enfatizar a associação dos testes na avaliação do paciente, destacar a complementariedade deles, minimizar as consequências negativas de laringoscopias repetidas. Keywords: Difficult airway, Airway, Intubation, Laryngoscopy, Mallampati test, Jaw-thrust maneuver, Palavras-chave: Via aérea difícil, Via aérea, Intubação, Laringoscopia, Teste Mallampati, Manobra de protrusão da mandíbula